Overview of Death Cases with Asphyxia Examined in the Forensic Medicine and Medikolegal Section of Dr. Moewardi Hospital 2017-2022 - Adji Suwandono; Yahya 'Ammar Yaritsul Firdaus (Cerdika: Jurnal Ilmiah Indonesia, 2024)
Asphyxia is the third most common case in forensics. Death from asphyxia can occur due to murder, accident, or suicide. This study aims to determine the description of death cases with asphyxia. This research is a descriptive research with observational study. The data collection technique used was total sampling with a sample of all cases of death with asphyxia examined at Dr. Moewardi Hospital in the period 2017-2022. From 2017 to 2022, there were 105 cases of death with asphyxia. The most cases were in 2020 (23%). The majority of victims were male (85%) and aged more than 50 years (39%). A total of 21 cases (20%) were strangulation asphyxia, 18 (17%) cases of suffocation asphyxia, 3 cases (3%) chemical asphyxia, 10 cases (10%) asphyxia due to disease, and 53 (50%) cases were other asphyxia. Signs of cyanosis were found in 91% of cases, petechiae in 56% of cases, edema in 2% of cases, and fine foam in 13% of cases. The most victims were found indoors with 48 cases (46%), followed by outdoors with 46 cases (44%), and in transportation with 1 case (1%). The three regions that sent the most victims were Surakarta city (63%), Sukoharjo district (10%), and Karanganyar district (10%). Most cases occurred in 2020. Males are most common in asphyxia cases. Other asphyxia is the most common type of asphyxia. In the majority of cases, signs of cyanosis were found. The place where the victims were found was relatively the same between indoors and outdoors